The effect of abstraction degree in contemporary painting subjects on gallery visitors' appreciative responses: an aesthetic psychology approach - Mujiyono, Mujiyono; Haryanto, Eko; Gunadi, Gunadi; Syarif, Muhammad Ibnan (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
One of the main challenges in understanding contemporary paintings is their high degree of abstraction. Each painting simplifies and alters its subject's form, with varying degrees of similarity to objects from nature. This study aims to examine how the degree of abstraction in contemporary painting subjects affects visitors' appreciative responses using an aesthetic psychology approach. The study employs a mixed-methods approach with a multiple-case study design. Semarang Gallery and Sangkring Art Space, both reputable galleries known for their artistic collections and high visitor numbers, were selected for this study. An evaluative survey was conducted with visitors at each gallery using a standardized set of operational questions. Descriptive statistical analysis was applied to calculate the average appreciation scores for each structure within the aesthetic psychology framework. Qualitative data from interviews and observations were employed to explain and enrich the survey findings. A cross-case analysis was carried out to identify the similarities and differences in the tendencies of aesthetic psychological structures across the two galleries. The findings indicate that three types of contemporary paintings, each with a varying degree of subject abstraction, were appreciated by visitors at both Semarang Gallery and Sangkring Art Space across the affective, perceptual, and cognitive dimensions. Affective responses emerged as the most dominant, followed by perceptual and cognitive responses, with an insignificant difference level (p < 0.05). The finding suggests that the degree of abstraction in contemporary paintings does not significantly affect the public's ability to appreciate them, particularly in affective, perceptual, and interpretative responses.